Research on Soil Erosion - Godone, Danilo; Stanchi, Silvia (IntechOpen, 2012)
Soil loss for erosion is a natural phenomenon in soil dynamics, influenced by climate, soil intrinsic properties, and morphology, that can both trigger and enhance the process. Anthropic activities, like inappropriate agricultural practices, deforestation, overgrazing, forest fires and construction activities, may exert a remarkable impact on erosion processes or, on the other hand, contribute to soil erosion mitigation through a sustainable management of natural resources. The book is the continuation of previously published "Soil Erosion Studies"; it is organized in a unique section collecting nine chapters focusing on a variety of aspects of the erosion phenomena.